Characterization of human pegivirus infection in liver transplantation recipients. Issue 12 (4th August 2019) - Izumi, Takuma; Sakata, Kazuhito; Okuzaki, Daisuke; Inokuchi, Shoichi; Tamura, Tomokazu; Motooka, Daisuke; Nakamura, Shota; Ono, Chikako; Shimokawa, Masahiro; Matsuura, Yoshiharu; Mori, Masaki; Fukuhara, Takasuke; et al.
Abstract: Approximately 2% of healthy persons are infected with human pegivirus (HPgV). HPgV is transmitted via vertical, sexual, and blood‐borne routes. Recently, the association of HPgV infection with the risk of lymphoma was reported. Here, we examined the prevalence of chronic HPgV infection in liver transplantation (LT) recipients and patients with hepatectomy and the influence of HPgV infection after LT on clinical and perioperative factors. We enrolled 313 LT recipients and 187 patients with hepatectomy who received care at the Kyusyu University Hospital between May 1997 and September 2017. Of the 313 recipients and 187 patients enrolled in this study, 44 recipients (14.1%) and 2 patients (1.1%) had HPgV viremia, respectively. There was no significant association between HPgV infection and LT outcomes. Interestingly, one recipient was infected with HPgV during the peritransplant period, which was likely transmitted via blood transfusion because HPgV RNA was detected from the blood bag transfused to the recipient during LT. We reviewed the available literature on the prevalence HPgV infections in other organ‐transplanted patients and whether they impacted clinical outcomes. They also had the higher prevalence of HPgV infection, while it appears to be of low or no consequences. In addition, HPgV infection induced the upregulation of interferon‐stimulated gene (ISG) expression in peripheral blood mononuclear cells. LT recipients had higher HPgV viremia compared to patients with hepatectomy. Although HPgV infection was not associated with LT‐related outcomes, it induced ISG expression in recipients. Highlight: HPgV infection induced the upregulation of interferon‐stimulated gene (ISG) expression in peripheral blood mononuclear cells.